REPRESENTASI DOA SEBAGAI BENTUK KOMUNIKASI ISLAM DALAM LIRIK LAGU ADA TITIK-TITIK DI UJUNG DOA KARYA SAL PRIADI (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Afdal Hafiz Takar; Winda Kustiawan (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
Music functions as one of the most pervasive channels for transmitting human values, including those of a spiritual and religious character. This study investigates how the act of prayer (du'a) is represented as a mode of Islamic communication within the lyrics of the Indonesian indie song Ada Titik-Titik di Ujung Doa composed by Sal Priadi. Employing a descriptive qualitative approach grounded in Charles Sanders Peirce's triadic semiotic framework encompassing representamen, object, and interpretant the research systematically identifies and classifies semiotic signs as icons, indices, and symbols. Data were drawn from the song's official lyrics and supplemented by secondary literature on Peircean semiotics and Islamic communication theory. Three principal semiotic categories were identified. Iconic signs encode sincere devotional attention (ihtimam) through vivid visual imagery. Indexical signs point directly to established Prophetic worship practices, particularly the pre-sleep supplication (du'a qabla nawm), and to the ongoing process of forgiveness (al-'afw). Symbolic signs, most prominently the metaphor of 'dots at the end of a prayer,' embody submission (tawakkal), patience (shabr), and the value of mutual supplication (du'a li al-akh). The findings affirm that contemporary popular music can serve as an effective medium for Islamic da'wah.